FLORA DIVERSITY IN THE PROPOSED DELACOUR’S LANGUR SPECIES AND HABITAT CONSERVATION AREA, HA NAM PROVINCE - Thanh Tuan, Nguyen; Van Phe, Phung (Journal of Forestry Science and Technology, 2023)
The flora in the Proposed Delacour’s Langur Species and Habitat Conservation Area is quite diverse with 562 species belonging to 373 genera, and 126 families of 6 vascular plant phyla. Of which, Angiospermae is the most dominant with 513 species (91.28%), 348 genera (93.3%) of 106 families (84.13%); the next Polypodiophyta with 38 species (6.76%), 18 genera (4.83%), 14 families (11.11%); the Lycopodiophyta has 5 species (0.89%) belonging to 3 genera (0.80%) of 2 families (1.59%) and the Gymnospermae has 4 species (0.71%) belonging to 2 genera (0.54%) of 2 families (1.59%); the last two Equisetophyta and Psilotophyta both have only one species, one genus of one family. In the Angiospermae, Dicotyledoneae is more dominant than Monocotyledoneae. The ten most diverse plant families have 215 species, accounting for 38.26% and the ten most diverse genera have 66 species, representing 11.75% of the total species in the study area. The forest plant resources in the Proposed Delacour’s Langur Species and Habitat Conservation Area have a high diversity of use values and can be classified into 15 different use groups. In the research site, there is a total of 41 threatened plant species that need to be preserved, including 21 species listed in the Vietnam Red Data Book, 27 species listed in Decree No. 84/2021/ND-CP, and 7 species listed in the IUCN Red List.